Whatever happened to the metric system? : how America kept its feet - Marciano, John Bemelmans (Bloomsbury, 2014)
"Most of the rest of the world is on the metric system, and for a time in the 1970s America appeared ready to make the switch. Yet it never happened, and the reasons for that get to the root of who we think we are, just as the measurements are woven into the ways we think. John Marciano chronicles the origins of measurement systems, the kaleidoscopic array of standards throughout Europe and the thirteen American colonies, the combination of intellect and circumstance that resulted in the metric system's creation in France in the wake of the French Revolution, and America's stubborn adherence to the hybrid United States Customary System ever since."--Dust jacket.
Keywords: Metric system; Weights and measures : United States; Metric system : History; historia; mitat; mittayksiköt; Yhdysvallat